Hydromechanical mechanism behind the effect of pore size of porous titanium scaffolds on osteoblast response and bone ingrowth. (5th December 2019) - Ouyang, Pengrong; Dong, Hui; He, Xijing; Cai, Xuan; Wang, Yibin; Li, Jialiang; Li, Haopeng; Jin, Zhongmin
Abstract: The pore size of porous scaffold plays a critical role in bone regeneration, but its mechanism and optimal value remain unclear. This study investigated the effect of pore size on hydromechanical properties of porous scaffold and its correlation with cellular response and bone regeneration. Porous titanium scaffolds with similar porosity and different pore sizes (400, 650, 850, and 1100 μm) were fabricated by selective laser melting. Their hydromechanical properties were derived by computational fluid dynamics analysis. The MC3T3 cells were dynamic seeded and cultured on the scaffolds to evaluate the cellular response. The rabbit distal femoral condyle implantation models were used to assess the bone ingrowth. Results indicated that the permeability, flow velocity, and the inflow of fluid linearly increased with the pore size. The wall shear stress evaluated from 400 to 650 μm and then dropped. These changes induced various performances in cell penetration, adhesion, proliferation, and differentiation, and finally induced best bone ingrowth in scaffold with pore size of 650 μm. This study provided a new understanding of the effect of pore size on bone regeneration of porous scaffold from the perspective of hydromechanics and indicated the potential of combining computational simulation and laboratory experiments in future studies. Graphical abstract: Unlabelled Image Highlights: Increasing the pore size linearly increased the permeability, flow velocity, and inflow of fluid. The shear stress first increased and then decreased with the increase in pore size. The pore size significantly affected the cell penetration, adhesion, proliferation, differentiation, and bone ingrowth. The hydromechanical properties closely correlated with the cellular response and bone regeneration